Nilai Sosial dan Nilai Politik dalam Kumpulan Puisi Nyanyian Akar Rumput - Izwar, Muhamad; Rusdiawan, Rusdiawan; Gunayasa, Ida Bagus (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
This research is about the social values and political values of Wiji Thukul’s poems in the anthology Nyanyian Akar Rumput. Therefore, this research aims to describe the forms of social values and political values of Wiji Thukul’s poems in the anthology Nyanyian Akar Rumput. As for the method of data collection are literature studies and observations. Observation method is taken by reading and identifying. While descriptive analysis method is used to analyzing data. Based on the result of data analysis, the forms of social values of Wiji Thukul’s poems in the anthology Nyanyian Akar Rumput is about responsibility, caring, and justice. While the forms of political values is about struggle, persuasion, and protest.